Understanding Media Production, Paul Dwyer (2019). (1st June 2020) - Sexton, Max
Understanding Media Production, Paul Dwyer (2019)London and New York: Routledge, 232 pp., ISBN 978-1-13823-814-5, h/bk, USD 124